Intravenous thrombolysis in wake‐up stroke: real‐world data from the Austrian Stroke Unit Registry. (9th January 2019) - Krebs, S.; Posekany, A.; Ferrari, J.; Lang, W.; Sommer, P.; Gattringer, T.; Boehme, C.; Sykora, M.
Abstract : Background and purpose: Data on real‐world experience with intravenous thrombolysis (IV tPA) in wake‐up stroke (WUS) are limited. The aim of this study was to examine the efficacy and safety of IV tPA in patients with WUS included in the Austrian Stroke Unit Registry. Methods: Data from a large nationwide stroke unit registry including initial stroke severity, vascular risk factors, comorbidities, treatment with IV tPA, symptomatic intracerebral haemorrhage (sICH) and functional outcome were extracted and analysed. Patients with WUS were compared with patients with known‐onset stroke (KOS) regarding the frequency of IV tPA treatment, neurological improvement (National Institutes of Health Stroke Scale score ≥4), sICH and 3‐month functional outcome by modified Rankin Scale score using standard statistical tests. Results: A total of 107 895 stroke patients entered the analysis, including 12 534 with WUS and 91 899 with KOS. Altogether, 904 (7.2%) patients with WUS received IV tPA as compared with 16 694 (18.2%) patients with KOS. Patients with WUS who received IV tPA treatment had twofold higher initial National Institutes of Health Stroke Scale score (median 8 vs. median 4) as compared with patients with KOS. There was no statistical difference in functional outcome by modified Rankin Scale score 0–1 at 3 months between patients with WUS and patients with KOS treated with IV tPA (adjusted odds ratio, 1.08; 95% confidence interval, 0.9–1.31). Also, the rate of sICH did not differ (4.1% vs. 4%, P = 0.852). Conclusions: In this large non‐randomized comparison, the safety and efficacy of IV tPA in patients with WUS in the real‐world setting seems to be comparable to patients with KOS.